Use of fine needle aspiration cytology for investigating lymphadenopathy in HIV positive patients. Issue 6 (June 1993) - Martin-Bates, E; Tanner, A; Suvarna, S K; Glazer, G; Coleman, D V
Abstract : The cytological diagnoses of 27 lymph node aspirates were compared with the histological diagnoses or clinical outcome in 23 HIV positive patients. There was agreement between the cytological and histological diagnoses in 14 of the 16 surgically biopsied cases. The clinical outcome in the remaining 11 cases was consistent with the cytodiagnosis. Fine needle aspiration (FNA) is a reliable, minimally traumatic, cost effective method with high specificity. It is suitable for an initial rapid diagnosis in HIV positive patients with lymphadenopathy.